Pengembangan Buku Penuntun Praktikum Klasifikasi Makhluk Hidup dengan Model Argument Driven Inquiry (ADI) - Umi Nurkhasanah; Neni Hasnunidah; Arwin Achmad (Universitas Lampung, 2018)
The lab workbook was used to support laboratory activities. This study aims to describe the validity and practicality of the guide book of classification of living creatures developed with ADI model. The research design was R D with 4-D model covering define stage, design, develop, and disseminate but disseminate not done. The practical lab book was made with a bright cover and a Franklin Gothic Book letter. Each practicum guide consists of a practical title, basic theory, objectives, research questions, tools, materials, work steps, argumentation schemes including claims, data, warrants, backing, argumentation sessions, and reports. Expert and practitioner validation test results are categorized as